Strategi Berbahasa Framing dalam Pemberitaan Aksi Penolakan Tunjangan Anggota DPR pada Detik.com - Ulya, Aqilah Iffatul; Anshori, Dadang S.; Kusumah, Encep (Jurnal Bahasa dan Sastra, 2026)
The action of rejecting the DPR allowances has sparked a variety of perspectives in media coverage, one of which is reflected in the language used to report on the protests. This study aims to analyze the language used by detik.com in framing the rejection of DPR allowances and explain how the use of language shapes certain meanings and biases in news coverage. This study uses a qualitative approach with data collection techniques in the form of documentation and note-taking. The data consists of five detik.com news articles that were purposively selected related to the rejection of the DPR allowance during the period of August 25—30. The analysis was conducted by classifying language elements (diction, phrases, clauses, sentences, coherence, and themes) based on Pan and Kosicki's four framing structures (syntax, script, thematic, and rhetorical). The results of the study show the dominance of the use of diction that implies rioting, the composition of titles that emphasize chaos, and narratives that focus on the destructive actions of the masses so that in the news, the action is framed as rioting in public spaces. This study concludes that the five news reports not only use language as a tool to communicate reality, but also symbolically to construct and delegitimize the action of rejecting the DPR allowance through negative framing in their reporting. These findings enrich the application of Pan and Kosicki's framing model in the analysis of political media discourse in Indonesia and are expected to serve as material for reflection for journalists in their use of language and in constructing balanced narrative structures so as not to appear to delegitimize social protest actions.